ЭТНОГРАФИЧЕСКИЕ ОСНОВЫ СВАДЕБНЫХ ПЕСЕН «ҲӘЎЖАР» - Бекжанова, Б. (SCIENCE and SOCIETY, 2018)
Karakalpak wedding-ritual folklore is an important historical and ethnographic source for the study of the genesis of the Karakalpak ethnic culture. The article deals with the folk songs "Khaujar" which are performed at the wedding ceremonies by bridesmaids to wish a happy marriage to a bride. The author approached to the theme from the point of view of the historical and ethnographical analysis.
Keywords: customs and rites; tradition; wedding; bride's farewell; folklore; wedding-ritual songs -"Khaujar"